Central Interleukin-1β Suppresses the Nocturnal Secretion of Melatonin - A. P. Herman; J. Bochenek; K. Król; A. Krawczyńska; H. Antushevich; B. Pawlina; A. Herman; K. Romanowicz; D. Tomaszewska-Zaremba (Mediators of Inflammation)
In vertebrates, numerous processes occur in a rhythmic manner. The hormonal signal reliably reflecting the environmental light conditions is melatonin. Nocturnal melatonin secretion patterns could be disturbed in pathophysiological states, including inflammation, Alzheimer’s disease, and depression. All of these states share common elements in their aetiology, including the overexpression of interleukin- (IL-) 1β in the central nervous system. Therefore, the present study was designed to determine the effect of the central injection of exogenous IL-1β on melatonin release and on the expression of the enzymes of the melatonin biosynthetic pathway in the pineal gland of ewe. It was found that intracerebroventricular injections of IL-1β (50 µg/animal) suppressed (P<0.05) nocturnal melatonin secretion in sheep regardless of the photoperiod. This may have resulted from decreased (P<0.05) synthesis of the melatonin intermediate serotonin, which may have resulted, at least partially, from a reduced expression of tryptophan hydroxylase. IL-1β also inhibited (P<0.05) the expression of the melatonin rhythm enzyme arylalkylamine-N-acetyltransferase and hydroxyindole-O-methyltransferase. However, the ability of IL-1β to affect the expression of these enzymes was dependent upon the photoperiod. Our study may shed new light on the role of central IL-1β in the aetiology of disruptions in melatonin secretion.